(untitled) (Vietnam Journal of Community Medicine, 2024)
Objective: The study was conducted to determine the clinical and subclinical symptoms of Chlamydia trachomatis (C. trachomatis) infection among infertile women treated at the National Hospital of Obstetrics and Gynecology (2020 - 2021). Methods: The study was designed using descriptive and analytical research method. Results: Among 119 infertile women infected with C. Trachomatis, the most common symptoms included increased vaginal discharge (67.22%), followed by abdominal pain (40.34%), genital itching (21.01%), decreased sexual arousal (16.81%), vaginal burning (15.13%), painful or difficult urination (15.13%), and abnormal vaginal bleeding (5.88%). The prevalence of vaginitis and cervicitis in infertile women infected with C. Trachomatis was 75.63% and 80.67%, respectively. Results of analyzing the subclinical characteristics of 119 infertile women infected with C. Trachomatis showed that: 100% of the women were co-infected with at least 1 Gram-positive/ Gram-negative organism, and Candida sp. 45.45% of the women had blocked fallopian tubes; and 37.82% had images of polycystic ovaries, abnormal uterine masses and hydrosalpinx. Conclusions: Typical clinical symptoms of infertile women were increased vaginal discharge, abdominal pain, gential itching... 100% of the women were co-infected with Ch. trachomatis and other organisms. 45.45% of the women had images of blocked fallopian tubes, and 37.82% had ultrasound images of abnormality in the reproductive tract.